A study on the probabilistic quantification of heavy-truck crash risk under the influence of multi-factors. (September 2022) - Baikejuli, Muladilijiang; Shi, Jing; Hussain, Muhammad
Highlights: A novel methodology for quantifying the heavy-truck crash risk caused by multi-factors is presented. A novel risk index of multi-factor crashes is derived for developing a criterion for crash risk quantification. Heavy-truck crash risk increases significantly with the increase of the number of risk factors involved in a crash. The multi-factor interaction between environmental factors and vehicular factors makes a considerable incremental contribution to the crash risk. Abstract: In order to manage and reduce a specific risk, its quantitative analysis is necessary. The key objective of this study is to illustrate the prevalence of multi-factors in fatal crashes involving heavy trucks and to quantify the crash risk under the influence of multi-factors. Data from a recent, nationally representative sample of fatal crashes was investigated to identify the risk factors contributing to crash causations and a novel risk index was obtained to develop a criterion for crash risk quantification. Then, based on the mutual information theory, the mutual dependence between risk factors was calculated to quantify the crash risk under different risk factor combinations. The results reveal that most heavy-truck fatal crashes are the result of co-occurring multi-factors rather than a single factor, and are mainly caused by simultaneous occurrence of two or three contributing factors. Moreover, crash risk increases with the increase of the number of risk factors influencing the driver. Furthermore, multi-factor interaction between certain risk factors, such as environmental and vehicular factors, makes incremental contribution to the crash risk by further increasing the crash probability. Specifically, when driver's aberrant behaviors (errors and/or violations) are exposed to both environmental and vehicular factors, driver's likelihood of being involved in a fatal crash increases significantly. This suggests that in addition to the number of risk factors, the crash risk also depends on the multi-factor interactions between different risk factors. Therefore, the effects of individual risk factors should be controlled at the outset to prevent the incremental effects of multi-factors on crash risk, in turn enabling risk minimization..